Fish farmers' perspectives and practices in aquaculture antimicrobial resistance (AMR): a comprehensive review - Ali, Fazlin; Mahmud, Muhammad Mu'az; Chong, Chou Min; Song, Adelene Ai Lian; Zainudin, Zanurul Huzaima (Islamic Azad University, Damghan Branch, 2024)
The increased use of antibiotics in aquaculture for disease management has raised concerns around antimicrobial resistance (AMR), which might threaten the industry's viability. Understanding fish farmers' viewpoints, and the critical player in aquaculture is crucial to addressing global seafood demands. This comprehensive literature review examines and explores the fish farmers' perceptions and responses to AMR. Important topics including antibiotic use, farmers' AMR knowledge, and disease control efficacy will be reviewed. The review illuminates various viewpoints to aid sustainable and responsible aquaculture decision-making.